Position Observations of NEAs at the RTT150 - Aslan, Zeki; Ivantsov, Anatoliy V.; Gumerov, Rustem I.; Hudkova, Lyudmila A.; Khamitov, Irek; Pinigin, Gennadiy I. (Amer Inst Physics, 2 Huntington Quadrangle, Ste 1No1, Melville, Ny 11747-4501 USA, 2008)
In 2004-2007, 560 observations of 17 Near-Earth Asteroids of 15-21 magnitudes were made at the Russian-Turkish telescope (RTT150). The reduction was made using reference stars from the UCAC2 and USNO-B1 catalogues. The comparison of the observed and calculated positions of the asteroids using the HORIZONS system gave standard errors of a single position in the range 0.05 divided by 0.50 ''. Analysis of the (O - C) is given in this paper.
Keywords: Asteroids; Astrometry